A multi -step curve search algorithm in nonlinear optimization - Duranovic-Milicic, N.I. (Yugoslav Journal of Operations Research; Vol 18 No 1 (2008): Vol. 18 No. 1, 2016)
In this paper a multi-step algorithm for LC1 unconstrained optimization problems is presented. This method uses previous multi-step iterative information and curve search to generate new iterative points. A convergence proof is given, as well as an estimate of the rate of convergence.